Squeal and Squawk : Barnyard Talk - Susan Pearson (New York, NY, United States Two Lions, 2004)
Cows give us milk, for ice cream and cheese. But my dog gives me kisses, and tail wags ... and fleas. Welcome to the barnyard! Eighteen rollicking poems explore the lives of farm animals. From a limerick about a rooster in love with a duck to an ode to the lazy life of a cow, these comically illustrated rhymes take a humorous look at our squealing and squawking animal friends
Keywords: Poetry -- Poetry